Finite element modeling of axially loaded concrete columns with metal sheet confinement - Nitchanun Hongsinlark; Maetee Boonpichetvong; Tanyada Pannachet (KKU Engineering Journal, 2014)
This paper proposed a nonlinear finite element model to investigate mechanism and behavior of the concrete columns confined with metal sheet. Three dimensional modeling was chosen. Concrete was modeled using the Drucker-Prager yield criterion and a softening function, whereas the Von-Mises yield criterion was chosen for metal sheet. Between both materials, a set of interface elements was inserted to represent layers of the bonding material. The results showed that the finite element model could model the behaviors that were observed from the laboratory experiments, and could capture the mechanisms that were not noticed in the laboratory experiment as well.